Patterns of policy learning in the RIS3 processes of less developed regions. Issue 3 (4th March 2021) - Bellini, Nicola; Lazzeri, Giulia; Rovai, Serena
ABSTRACT: The implementation of the Smart Specialisation approach was expected to require an especially challenging commitment to policy learning in less advanced regions compared with advanced ones. This paper suggests a partially different analytical framework by discussing the relevance of path dependency in the design and implementation of Research and Innovation Strategies for Smart Specialisation (RIS3). The research question concerns the relationship between previous experiences in innovation policy also in less advanced regions and RIS3 policy processes. Based on the two case studies of Sicily and Apulia (Italy), the paper investigates in which way policy heritage contributed to the quality of processes and outcomes.